Selected biological properties of quercetin, curcumin, and kaempferol - Wielgus, Małgorzata; Zaniewicz, Nikola (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2024)
Polyphenols are a large group of organic compounds present in plants, where they play various roles pivotal to their proper physiological functioning. Polyphenols are ubiquitous in many dietary sources such as fruits, vegetables, beverages, seeds, and honeys. Diet plays a crucial role in sustaining overall well-being of the organism and preventing diseases, including cancer. Despite broad spectrum of health promoting activity of polyphenols, such as antioxidant, anti-inflammatory and antimicrobial, many of them are also potent anti-cancer compounds. In this review we focused on presentation of three polyphenols such as quercetin, curcumin, and kaempferol. We discussed recent studies concerning their beneficial impact on human health and potential as anticancer agents.